Optimization of the flow characteristic in various array arrangements of multiple picohydro power turbines - Sahat, Idris Mat; At-Tasneem, Mohd Amin; Mu'Tasim, Muhammad Ammar Nik; Hassan, Wan Anuar Wan; Jamaludin, U. K.; Rosli, Rosmazi (2017)
Renewable energy is an energy which is generated from the natural resources such as wind, water, sunlight, rain and geothermal. Naturally, it can be replenished. This energy can reduce the pollutions that occur all around the world. It is also can be the best solution for the global issue such as climate changes that is happened rapidly nowadays. Likewise, it is practically suitable in the rural areas or the remote areas because of the difficulty in getting fuel which is also expensive. Micro hydropower (MHP) is one of renewable energy resources in the world. Hydro turbines are used to change water pressure from river flow into mechanical or kinetic energy, which can generate electricity. It can be classified by its capacity such as pico, mini, and small which the power are up to 100KW, 1MW and 25MW respectively. Accordingly, MHP is the most economical technology to generate power. This is because MHP use the water flow in a river to generate power, where it is a continuous process. Besides, the costs for manufacture and install MHP turbines are cheaper compared to the tidal and wind turbines. Most of the computational researches on arrays arrangement are done for tidal turbines, which is almost similar to MHP turbines. Computational Fluid Dynamics (CFD) models are used to analyze the wake effects in arrays of tidal turbines. The simulations of the turbines are done to obtain the wake characteristics of actuator disc and compare with experimental data. According to, Fluent software is used to simulate 3-D models of Tidal Energy Converter (TEC) turbines with three-row array. In this research, the TEC array arrangement and spacing simulated to identify the performance variation of electrical power output. Besides that, adaptive mesh method with Gerris solver is used to optimize multiple arrays of picohydro turbines in a channel. Reynolds-averaged Navier Stokes (RANS) equations are used with the turbines to stand for frozen rotor. Static blade method is similar with the frozen rotor method. The frozen rotor method is used in the computational domain to consider effect of velocity on it. The CFD software is used here to analyse the best 3D array arrangement of river picohydro turbines, which generate maximum power output. Meanwhile, the MATLAB and DasyLab simulations will validate the CFD results obtained from a single picohydro turbine at three different locations.